THE EFFECT OF TAXPAYER AWARENESS ON TAXPAYER’S COMPLIANCE (CASE STUDY : UMKM USERS OF E- COMMERCE BEC IN BANDUNG CITY) - Ayuningrat, Siti Maulida Putri; Yustiani, Ellya; Fadlila, Nadhifah Tasya; Dzulhayani, Nurani; Devega, Lidya; Arsalan, Syakieb (CENTRAL ASIA AND THE CAUCASUS, 2022)
In this study to find out how the effect of taxpayer awareness on taxpayer compliance (a case study on UMKM using E-Commerce BEC in Bandung City). Data in this study were obtained from UMKM taxpayers who use E-Commerce BEC in Bandung City who are willing to become respondents. This study uses source of primary data and secondary data by conducting direct research by distributing questionnaires to many as 52 respondents. The results of this study indicate that taxpayer awareness has a positive and significant effect on taxpayer compliance in paying taxes because the higher taxpayer awareness, the higher taxpayer compliance.